Fluoroalkyl-grafted methacrylate-PDMS membranes using fluoromonomer as a diluent for enhancing biobutanol pervaporation. Issue 18 (19th August 2021) - Si, Zhihao; Wang, Yaqi; Liu, Chang; Xue, Tanlong; Yang, Shuai; Li, Guozhen; Zhang, Changwei; Chen, Bo; Cai, Di; Qin, Peiyong
Abstract : The green and ultrafast preparation of PDMS membrane is realized by using fluoromonomer as the diluent, and the anti-biofouling of membrane is simultaneously improved. Abstract : In bioalcohol production, alcohol-permselective membranes have an important role to play in the growing demand for biofuels, where polydimethylsiloxane (PDMS) membranes are considered as a benchmark of alcohol-permselective membranes. However, two key technical barriers still need to be addressed, i.e., (i) the long curing time and the use of toxic solvents hamper their large-scale application and (ii) the trade-off between pervaporation performance and anti-biofouling ability limits the separation of biobutanol from fermentation broths. To overcome these bottlenecks, in this study, a UV-polymerizable fluoromonomer (F-monomer) is introduced into a methacrylate-PDMS (MA-PDMS) membrane-forming system instead of toxic solvents. The green and ultrafast membrane preparation (31–72 s) via UV polymerization is realized. The results indicate that the fluoroalkyl groups –(CF2 )6 of the F-monomer enhance the hydrophobicity of the membrane surface, yielding a high water contact angle of 112°. Compared with an MA-PDMS membrane, the as-prepared MA-PDMS-F membranes were found to have a simultaneously enhanced membrane flux (862–1216 g m −2 h −1 ) and separation factor (34–41) when used in the separation of a butanol/water binary solution. Importantly, the MA-PDMS-F membrane surface weakly interacts with microbes in the fermentation broth because of its much lower polarizability, which leads to an outstanding anti-biofouling ability.